(3eQGJH GdCUhd hZQGFH GdaUhd aj GdbQGBJs - (3Yde GdOjf Ydj Hf eMeO GdSNGhj,J (B643 (3g` s
(3ChdgG (B:s
(3MOKfi CHh GdeXaQ ajQhR GdLhgQi cGf QShd Gddg Udi Gddg Ydjg hSde CLhO GdfGS hcGf CLhO eG jchf ai QeVGf Mjf jdbGg LHQjd ai cd djdI ef QeVGf s
(3BNQgG (B:s
(3hQhi Yf CHj MfjaI QMeg Gddg Cfg cGf jbQC GdbQCf ai QcYI aYd Pdc KdGKjf SfI QVi Gddg JYGdi Yfge CLejYf s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B332s
(3eUOQ GbJfGA GdCUd (B:s
(3GdRjOGfjI ef GdNRGfI GdedcjI HeOjfI GdQHGW (B(4676) s
Keywords: (3GdbQGAGJ hGdJLhjOs